Role of fiscal policy in the economic restructuring of Singapore. - Lim, Hwee Lin. (2008)
The government plays a dominant role in the restructuring of the Singapore economy. It has successfully managed Singapore's economy through 3 major crises in 1973, 1985 and 1997 by providing financial and tax incentives to stimulate the economic sectors, creation of the Growth Triangle and the move towards Knowledge-Based Economy.